Universal principles of design : 125 ways to enhance usability, influence perception, increase appeal, make better design decisions, and teach through design - Lidwell, William; Butler, Jill , 1969-; Elam, Kimberly , 1951-; Holden, Kritina (Rockport Publishers, 2010)
A cross-disciplinary reference of design. Pairs common design concepts with examples that illustrate them in practice